2015
DOI: 10.1037/dev0000035
|View full text |Cite
|
Sign up to set email alerts
|

Change and predictors of change in parental self-efficacy from early to middle adolescence.

Abstract: Parental self-efficacy (PSE) describes parents' beliefs about being able to handle developmentally specific issues and being able to influence their child in a way that fosters the child's positive development and adjustment (Bandura, 1997). Parents of adolescents have been shown to feel less efficacious than parents of preadolescent children (Ballenski & Cook, 1982), but little is known about the factors behind low levels of PSE among parents of adolescents. This study examined mean-level changes in PSE and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 67 publications
(121 reference statements)
8
70
2
6
Order By: Relevance
“…Ethnicity is one particularly interesting parenting context that has been found to be related to parental confidence, particularly for African American parents. In a longitudinal study of almost 400 parents of adolescents, Glatz and Buchanan (2015) found that higher levels of parenting efficacy were reported by African American parents versus White parents, but that these levels declined over time. Similarly, Hill and Tyson (2008) found that at initial assessment when the children were in Kindergarten, African American mothers reported higher parenting efficacy than White mothers, even considering multiple contextual factors.…”
mentioning
confidence: 99%
“…Ethnicity is one particularly interesting parenting context that has been found to be related to parental confidence, particularly for African American parents. In a longitudinal study of almost 400 parents of adolescents, Glatz and Buchanan (2015) found that higher levels of parenting efficacy were reported by African American parents versus White parents, but that these levels declined over time. Similarly, Hill and Tyson (2008) found that at initial assessment when the children were in Kindergarten, African American mothers reported higher parenting efficacy than White mothers, even considering multiple contextual factors.…”
mentioning
confidence: 99%
“…This measure has been used in previous studies and has shown to predict parenting practices (Glatz and Buchanan 2015a, b). Parents rated how much they thought they could influence the target adolescent, and the following are example items: “To get the child to stay out of trouble in school,” and “To prevent the child from doing things they do not want him or her to do outside the home.” Parents responded on a Likert scale ranging from 1 ( Very little ) to 7 ( A great deal ).…”
Section: Methodsmentioning
confidence: 99%
“…We focused on early adolescence, as this is a time when PSE is at especially low levels (Ballenski and Cook 1982; Glatz and Buchanan 2015b), which have been shown to have negative consequences for parenting practices among parents of children in this age range (Glatz and Buchanan 2015a). We expected that higher levels of PSE would predict more promotive parenting especially when parents face more difficult behaviors in the target adolescent.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of mood and anxiety disorders during this critical period of development can result in deleterious consequences, such as impairing social, emotional, and functional development, as well as increasing the likelihood of school absences and suicide (Asselmann, Wittchen, Lieb, & Beesdo‐Baum, ; Carballo et al., ; Lawrence et al., ). For parents, even if their children do not experience such disorders, the task of guiding their offspring from childhood to adolescence can be daunting, and the early adolescent developmental period marks a low point in parental confidence in their parenting abilities (Glatz & Buchanan, ). Parents continue to play an important role in providing adolescents with the structure and support they require to flourish during a time of rapid neurological, physical, emotional, and social change (Patton et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The 15 items in the adolescent subsection assess parental comfort in managing tasks such as “dealing with your child's moodiness,” “helping your child to leave home,” and “helping your child establish some direction in his/her life.” The items were developed based on parenting books, primarily those by Duvall () and Havighurst (). The adolescent subsection of this measure has been used in several recent studies (e.g., Glatz & Buchanan, , ) and is helpful in measuring PSE in relation to managing adolescent behaviors and helping adolescents to reach their developmental milestones. However, it does not include items assessing PSE in relation to parenting behaviors that recent research has suggested are important in preventing internalizing disorders in adolescents, such as parental warmth and involvement (Yap et al., ).…”
Section: Introductionmentioning
confidence: 99%